The stress-induced metabolites changes in the flavor formation of oolong tea during enzymatic-catalyzed process: A case study of Zhangping Shuixian tea. (15th October 2022) - Wu, Liangyu; Wang, Yahui; Liu, Suhui; Sun, Yun; Li, Chenxue; Lin, Jinke; Wei, Shu
Highlights: 980 non-volatile and 157 volatile metabolites were identified. An integrated metabolites-proteins pathway network was constructed. The electronic-sensory were used to explore flavoring-compounds. Abstract: To interpret the environmental stresses induced dynamic changes of volatile and non-volatile constitutes in oolong tea leaves during enzymatic-catalyzed processes (ECP), metabolomic and proteomic studies were carried out using the processed leaf samples collected at the different stages of ECP for Zhangping Shuixian tea manufacture. Non-processed leaves were applied as control. Out of identified 980 non-volatiles and 157 volatiles, 40 non-volatiles and 8 volatiles were screened out as biomarkers, respectively. The integrated analysis on metabolites-proteins showed that phenylpropanoid biosynthesis, flavonoid biosynthesis, and phenylalanine metabolism were significantly enriched and highly correlated to the dynamic changes of key metabolites during ECP stage. A biological pathway network was constructed to illuminate the enzymatic-catalyzed production of critical flavoring compounds, including carbohydrates, amino acids, flavonoids, and volatile phenylpropanoids/benzenoids. The electronic-sensory analyses indicated leaf dehydration and mechanical wounding occurred over the sun-withering and turning-over steps are indispensable to form characteristic flavor of Shuixian tea.